Le luxembourgeois, enfant naturel de la Seconde Guerre mondiale - Nicolas Lefrançois (Lengas)
The Grand Duchy of Luxembourg is a trilingual state in which all residents have the choice of using Luxembourgish, French or German to express themselves since the Law on the Language Regime of the 24th of February 1984 which recognizes and ratifies their official and unlimited coexistence. However, the Luxembourgish language, as the only national language of Luxembourg, has undergone a recent quality change in the country's history. From simple oral and regional variety of the High German, it acquired the status of language to support an identity and political demand of the population during the Second World War: to dissociate itself from Nazi Germany and to affirm its cultural peculiarity. The analysis of the Luxembourg case then raises the question of language not only from the point of view of its morphology but also of its socio-political role.